FRAME MODEL OF ENGLISH VERBS FOR INFORMING (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-3-32-43The article presents a frame modeling of English verbs of true and false information. Verbs of true information include the verbs: confirm, confess, admit, avow, assure, assert, affirm, aver, claim, plead, acknowledge, concede, verify, attest, dispel, maintain, contend, predict, certify, vouch, and verify. Verbs of false information: lie, deceive, deny, debunk, misinform, mislead, misreport, concoct, bluff, controvert, misrepresent, beguile, malign, fib, equivocate, fudge, invent, perjure, snow, profess, trick, fox, fabricate, prevaricate. Frame modeling implies identifying frames and their constituent subframes, with additional components. First of all, verbs of true information form the frame “truth” and, accordingly, verbs of false information form the frame “lie”. As a result of the analysis, the “truth” frame consists of the “truth-confession”, “truth-statement”, “truth-announcement”, and “truth-proof” subframes. The “truth-confession” subframe is characterized by the recognition of the truth, most often reluctantly, and is represented by verbs such as avow, concede, admit, confess, and acknowledge. The “truth-statement” subframe is expressed by the following verbs: aver, assert, affirm, vouch, aver, claim, assure, plead, maintain, verify. The “truth-announcement” subframe is represented in the verbs contend, predict, certify, and avow. The “truth-proof” subframe is formed by the verbs attest, confirm, dispel, verify. The “lie” frame includes the “lie-denial”, “lie-fantasy”, “lieconcealment”, “lie-misinformation”, and “lie-persuasion” subframes. The “lie-negation” subframe: deny, debunk, controvert. The “lie-fantasy” subframe: invent, assume, concoct, fabricate. The “lieconcealment” subframe: deceive, equivocate, snow, prevaricate. The “lie-misinformation”: misinform, misreport, lie, misrepresent, fib, fudge, malign, perjure. The “lie-persuasion” subframe: mislead, beguile, deceive, fox, bluff, trick.Key words: frame, verbs, cognitive load, truth, lie